The Impact of Bullying on Adolescent Mental Health: A Literature Review - Dhita Kurnia Sari; Reni Nurhidayah (Journal of Health Science Community, 2025)
Bullying is a pervasive social problem affecting adolescents worldwide and has been identified as a major risk factor for the development of mental health disorders. This literature review explores the impact of bullying on adolescent mental health by analyzing findings from recent academic studies. The review highlights associations between bullying victimization and psychological outcomes such as depression, anxiety, suicidal ideation, low self‑esteem, and long‑term psychiatric vulnerabilities. Additionally, this review provides a deeper examination of the mechanisms through which bullying influences psychological functioning, including emotional dysregulation, chronic stress exposure, and impaired social development. The analysis also considers contextual factors such as family environment, school climate, and digital media use that may exacerbate or buffer the mental health consequences of bullying. Overall, the findings emphasize the need for early intervention, school‑based prevention programs, supportive peer networks, and accessible mental health services to reduce the psychological burden on adolescents and prevent long‑term harm.